Penyuluhan Tanaman Cincau Untuk Meningkatkan Perekonomian Warga Dusun Sumbersari Desa Mojojajar Kecamatan Kemlagi Kabupaten Mojokerto - Fajar Budiyanto; Ahfi Nova Ashriana; Elly Joenarni; Diah Cahyani; Trijadi Herdajanto; Mochamad Irfan; Yusuf Rahman Al Hakim; Dwi Sembe Sigita (LPPM Universitas 17 Agustus 1945 Semarang, 2024)
This community service was carried out in Sumbersari Hamlet, Mojojajar Village, Kemlagi District, Mojokerto Regency, with the aim of increasing the community's knowledge and skills in cultivating grass jelly plants to boost their economy. Community service activities last for 3 months and use counseling and mentoring methods. Counseling is carried out by providing material about the cultivation of grass jelly plants, including planting, maintenance and harvesting techniques to converting them into economically valuable products such as grass jelly ice and organic fertilizer from grass jelly waste. Mentoring is carried out by helping the community apply the material that has been presented in the counseling. The results of community service show a significant increase in community knowledge and skills in cultivating grass jelly plants after participating in counseling and mentoring. This is proven by the increasing number of participants who succeeded in harvesting grass jelly and their harvests. This increase also has a positive impact on the economy of the people of Sumbersari Hamlet, as can be seen from the increase in their average monthly income. The success of this community service shows that grass jelly cultivation can be a promising business alternative to improve the economy of rural communities. This community service program can be replicated in other areas with similar conditions.